2007
DOI: 10.2984/1534-6188(2007)61[533:vdofla]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Fish Larvae and Its Relation to Water Column Structure in the Southwestern Gulf of California1

Abstract: The seasonal evolution of vertical distribution of fish larvae and its relationship with seasonal stratification, as measured by a quantitative stability parameter, were analyzed for a region off Bahía de La Paz in the southwestern Gulf of California. Samples were obtained with an opening-closing net (505 mm) in 50-m depth strata from surface to 200-m depth in May, July, and October 2001 and February 2002. Significant differences in total larval abundance and in dominant species (mesopelagic and epipelagic) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…This stratified technique has been used successfully in previous studies (e.g. Espinosa-Fuentes and Flores-Coto, 2004;Sánchez-Velasco et al, 2007).…”
Section: Field and Zooplankton Samplingmentioning
confidence: 94%
“…This stratified technique has been used successfully in previous studies (e.g. Espinosa-Fuentes and Flores-Coto, 2004;Sánchez-Velasco et al, 2007).…”
Section: Field and Zooplankton Samplingmentioning
confidence: 94%
“…To obtain a representative mean of the physical variables in the water column in each sampling station, we chose the depth of the 24.5 kg m −3 isopycnal, as a good indicator of the thermocline depth. In studies of the vertical distribution of fish larvae it is observed that most of the larvae were found in and above the thermocline [ Loeb and Nichols , ; Sánchez‐Velasco et al ., ; Danell‐Jiménez et al ., ]. On the other hand, Kessler [] in his review of the circulation of the Eastern Tropical Pacific argues that this isopycnal of 24.5 kg m −3 is one that best represents the seasonal movements of the pycnocline.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been taken in ichthyoplankton collections from the Gulf of California in water of depths of 200-2,000 m (Sánchez-Velasco et al 2007). While individuals of this species were found to be relatively abundant in Río Claro, Corcovado National Park, Costa Rica.…”
Section: Eleotris Pictamentioning
confidence: 98%